Financial governance and Indonesia’s Reforestation Fund during the Soeharto and post-Soeharto periods, 1989–2009: a political economic analysis of lessons for REDD+ - Barr, C.; Dermawan, A.; Purnomo, H.; Komarudin, Heru (Center for International Forestry Research, 2010)
This study analyses Indonesia’s experience with its Reforestation Fund, and examines implications for REDD+. The Reforestation Fund (Dana Reboisasi, DR) is a national forest fund financed by a volume-based timber levy to support reforestation and forest rehabilitation. Since 1989, the fund has had receipts of US $5.8 billion. During the Soeharto era, the Ministry of Forestry allocated more than US $1.0 billion in cash grants and loans from the Reforestation Fund to promote commercial plantation development. Many recipients fraudulently marked up their costs and overstated areas planted, causing the programme to fall well short of targets. The Ministry also disbursed US $600 million to finance politically favoured projects outside the Fund’s mandate of promoting reforestation and forest rehabilitation. A 1999 external audit by Ernst & Young documented billions of dollars in losses, citing systematic financial mismanagement. Since 1998, successive post-Soeharto governments have taken steps to improve financial governance by: transferring authority over the Reforestation Fund to the Ministry of Finance; strengthening the Supreme Audit Board’s authority to monitor public financial assets; and creating a Corruption Eradication Commission which has prosecuted dozens of senior officials. However, continuing problems with the Reforestation Fund hold significant implications for future REDD+ payment schemes. The study highlights how national strategies to manage both the Reforestation Fund and REDD+ funding streams must: strengthen financial management and revenue administration; deal with corruption, fraud, and loss of state assets; monitor, report, and verify financial transactions; remove misaligned and perverse incentives; ensure accountability and mitigating moral hazard; and distribute benefits equitably.